Perbandingan Hasil Belajar Matematika Peserta Didik MA Selama Pembelajaran Daring dan Pembelajaran Tatap Muka Pada Materi Dimensi Tiga - Umi Nurofi'atin (Mitra Pilar: Jurnal Pendidikan, Inovasi, dan Terapan Teknologi, 2024)
Abstract This study aims to analyze the comparison of mathematics learning outcomes of Madrasah Aliyah (MA) students during online and face-to-face learning on the topic of Three-Dimensional Geometry. Data were obtained from students' scores over three years (2021-2023). The year 2021 represents the period of fully online learning, while 2022 and 2023 reflect the transition to and implementation of face-to-face learning. Data analysis includes the highest score, lowest score, average, median, mode, and standard deviation. Results indicate that the highest average score was recorded in 2022 (75.46), while the lowest score occurred in 2021 (16). The highest standard deviation was observed in 2023 (22.00), indicating greater variation in learning outcomes compared to other years. The highest mode was recorded in 2023 (93.33), demonstrating an increase in the number of students achieving optimal scores. These findings suggest that face-to-face learning provides more stable and generally higher learning outcomes compared to online learning. This study offers implications for the development of adaptive learning strategies in the future, particularly in the context of mathematics education. Abstrak Penelitian ini bertujuan untuk menganalisis perbandingan hasil belajar matematika peserta didik Madrasah Aliyah (MA) selama pembelajaran daring dan tatap muka pada materi Dimensi Tiga. Data diperoleh dari nilai peserta didik selama tiga tahun (2021-2023). Tahun 2021 merepresentasikan masa pembelajaran daring penuh, sedangkan tahun 2022 dan 2023 mencerminkan transisi dan penerapan pembelajaran tatap muka. Analisis data mencakup nilai tertinggi, nilai terendah, rata-rata, median, modus, dan standar deviasi. Hasil menunjukkan bahwa rata-rata nilai tertinggi tercatat pada tahun 2022 (75,46), sedangkan nilai terendah pada tahun 2021 (16). Standar deviasi tertinggi terjadi pada tahun 2023 (22,00), mengindikasikan variasi hasil belajar yang lebih besar dibandingkan tahun lainnya. Modus tertinggi tercatat pada tahun 2023 (93,33), menunjukkan peningkatan jumlah siswa yang memperoleh nilai optimal. Temuan ini mengindikasikan bahwa pembelajaran tatap muka memberikan hasil belajar yang lebih stabil dan cenderung lebih tinggi dibandingkan pembelajaran daring. Penelitian ini memberikan implikasi bagi pengembangan strategi pembelajaran yang adaptif di masa depan, khususnya dalam konteks pembelajaran matematika.